Are workers more vulnerable in tradable industries? - Kent Eliasson; Pär Hansson (Örebro University School of Business, 2013)
Reduced trade barriers and lower costs of transportation and information have meant that a growing part of the economy has been exposed to international trade. In particular, this is the case in the service sector. We divide the service sector into a tradable and a non-tradable part using an approach to identify tradable industries developed by Jensen and Kletzer (2006). We examine whether the probability of displacement is higher and income losses after displacement greater for workers in tradable services and manufacturing (tradable) than in non-tradable services. We also analyze whether the probability of re-employment is higher for workers displaced from tradable services and manufacturing than from non-tradable services. We find that in the 2000s the probability of displacement is relatively high in tradable services in comparison to non-tradable services and manufacturing. On the other hand, the probability of re-employment is higher for those displaced from tradable services. The largest income losses e found for those who had been displaced from manufacturing. Interestingly, the income losses of those displaced from manufacturing seems mainly to be due to longer spells of non-employment, whereas for those displaced in tradable services lower wages in their new jobs compared to their pre-displacement jobs appears to play a larger role.
Keywords: F16; J62; J63; 330; displacement costs; re-employment; earnings losses; tradable services